Intramuscular Administration of Alfaxalone Alone and in Combination for Sedation and Anesthesia of Rabbits (Oryctolagus cuniculus) - Bradley, Michael P (J Am Assoc Lab Anim Sci, 2019)
This study compared alfaxalone, alone and in combination with other medications, for sedative and anesthetic properties after intramuscular administration in New Zealand white rabbits. In the main portion of the study, 6 female rabbits were assigned to 5 treatment regimens in a blinded crossover design. Alfaxalone (6 mg/kg IM) was administered alone and in combination with each of the following: 0.3 mg/kg butorphanol; 1 mg/kg midazolam; 0.2 mg/kg dexmedetomidine; and both 0.3 mg/kg butorphanol and 0.2 mg/kg dexmedetomidine. An additional 6 rabbits received 0.2 mg/kg dexmedetomidine for comparison. The median time to onset of recumbency ranged from 2.0 to 5.5 min, with times significantly shorter for animals that received alfaxalone with either midazolam or dexmedetomidine than for those given dexmedetomidine only. Duration of sedation (mean ± 1 SD) was: alfaxalone only, 40 ± 7.3 min; alfaxalone with butorphanol, 47.8 ± 9.9 min; alfaxalone with midazolam, 65.2 ± 6.5 min; alfaxalone with dexmedetomidine, 157.5 ± 22.4 min; alfaxalone with butorphanol and dexmedetomidine, 157.7 ± 22.3 min, and dexmedetomidine only, 93.7 ± 11.9 min. Response to noxious stimuli was absent in 2 of the rabbits given dexmedetomidine only, 4 of those given alfaxalone with dexmedetomidine, and all 6 of the animals dosed with alfaxalone, butorphanol, and dexmedetomidine; this last group displayed the longest absence of a toe-pinch response (57 ± 3 min).